2009
DOI: 10.1002/jbm.a.32551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaTiO3–CaCO3 prepared by alkoxide method on cell response

Abstract: In recent years, calcium titanate (CaTiO(3)) and carbon-containing materials have gained much attention in a number of biomedical material researches. To maximize the advantages of both materials, we developed a novel alkoxide method to get "calcium titanate with calcium carbonate" (CaTiO(3)-CaCO(3)). The objective was to evaluate the crystallinity and elemental composition of CaTiO(3)-CaCO(3) prepared by alkoxide method, CaTiO(3)-aC elaborated by modified thermal decomposition method, commercially-prepared Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…It is well known that carbon-containing materials improve biological response as we showed during previous studies of our group, where we demonstrated that calcium carbonate in CaTiO 3 -CaCO 3 has a good osteoblastic response 22) . Hence, here we examined the eff ect of diff erent amounts of CaCO 3 combined with CaTiO 3 on cell proliferation and osteoblastic response.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…It is well known that carbon-containing materials improve biological response as we showed during previous studies of our group, where we demonstrated that calcium carbonate in CaTiO 3 -CaCO 3 has a good osteoblastic response 22) . Hence, here we examined the eff ect of diff erent amounts of CaCO 3 combined with CaTiO 3 on cell proliferation and osteoblastic response.…”
Section: Discussionsupporting
confidence: 63%
“…6). Such eff ect was observed as well when KUSA/A1 cells were cultured in usual α-medium and in contact with CaTiO 3 -aC and HA during previous studies 22) . The increased mineralized areas observed in cultures with higher amounts of CaCO 3 might be caused by increased amounts of Ca 2+ released to culture medium.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The FTIR spectra were used to obtain the phonon energy of vibrational modes in the host. The phonon energies at 577 and 442 cm −1 are attributed to the characteristics of alkaline titanates and the Ti–O bond vibration of (TiO 3 ) 2− groups, respectively . After Li + doping, higher energy phonons appear at 716 cm −1 .…”
Section: Resultsmentioning
confidence: 98%